Penerapan Model Pembelajaran TPS (Think Pair Share) pada Materi Negara Maju dan Negara Berkembang untuk Meningkatkan Kemampuan Bertanya dan Hasil Belajar Siswa - Sunarto Sunarto (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This study aims to improve the ability to ask questions and student learning outcomes on material motion systems in humans in class IX D SMP Negeri 1 Nusawungu with cooperative learning model type TPS (Think Pair Share). This research is a type of Classroom Action Research (CAR) which is a research conducted systematically reflective of the actions taken by the teacher as a researcher, ranging from planning, implementing, to assessments to improve learning conditions. In this class action research researchers used two cycles, each of which consisted of four stages: planning, action, observation, and reflection. The research instrument was in the form of a test aimed at finding out student learning outcomes and non-tests in the form of an observation sheet filled out by collaborators, and a student motivation questionnaire sheet filled out by students. The subjects of this study were students of class IX D of SMP Negeri 1 Nusawungu, totaling 32 students. The data analysis technique used for the assessment process is quantitative descriptive to find out the improvement of student learning outcomes, and qualitative descriptions to determine students' asking abilities. The results of this class action research are the application of the TPS (Think Pair Share) learning model that provides an increase in the ability to ask questions and student learning outcomes from cycle I, cycle II sequentially having a percentage of graduation of 25% to 97% while the ability to ask students from 36% to 92%. so it can be concluded that the application of the TPS type learning model can improve the ability to ask questions and student learning outcomes.